Manfaat Penciptaan Tumbuhan Sebagai Penghasil Oksigen dan Karbohidrat Serta Relevansinya dengan Surah Al-An’am Ayat 99 - Sa’danah Femi Putri; Budi Rianto; Kelvin Nisra Ditya; Anjela Ulfa Ningsih; Ahmad Jamin; Oki Mitra (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
In this study, the research objective is to analyze the perspective of biology uztadzah regarding the benefits of creating plants as producers of oxygen and carbohydrates and their relevance to Surah Al-an'am verse 99. This research design is descriptive qualitative. The research instruments are in the form of observation sheets, questionnaires, and documentation. The subjects and objects of the research are 2 biology teachers, while the research objects include material objects including plants, oxygen, and carbohydrates, the formal object is Surah Al-an'am verse 99. Data collection techniques are observation and questionnaires. Data analysis techniques are in the form of data reduction, data presentation and drawing conclusions. The results and discussion are in the form of plants producing CO2, traditional medicine and food that can be processed and utilized by humans. Therefore, plants have many benefits for human life. Without plants, humans cannot live and develop. Plants are not toys but a life that must be preserved. The Qur'an, Surah Al-an'am verse 99 has long emphasized that Allah created plants to have many benefits for humans and not to be destroyed, but must be maintained. As educators, we should teach children about the importance of protecting the environment and its relevance as emphasized in the Al-Quran, Surah Al-Al'am, verse 99.